Suprasternal cross-sectional echocardiography in assessment of patient ducts arteriosus. - Smallhorn, J F (1982)
Ninety-four patients with patent ductus arteriosus, whose ages ranged from 28 weeks gestation to 8 years, were assessed by suprasternal cross-sectional echocardiography. A further group of 37 cases without a patent ductus arteriosus were assessed by the same technique. The appearances of the ductus via this approach varied according to the ventriculoarterial connections. Reliable assessment of patency was possibly in 87 cases. In seven cases where the ductal lumen was less than 2 mm in size, a false negative diagnosis was made. In the 37 patients without a patent ductus arteriosus, no false positive diagnoses were made. Suprasternal cross-sectional echocardiography enables a reliable assessment of ductal patency, provided the lumen falls within the range of lateral resolution of the equipment being used.